2015
DOI: 10.1111/dom.12486
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure‐lowering effect of the sodium glucose co‐transporter‐2 inhibitor ertugliflozin, assessed via ambulatory blood pressure monitoring in patients with type 2 diabetes and hypertension

Abstract: This study compared the blood pressure-lowering effect of ertugliflozin (1, 5, 25 mg), hydrochlorothiazide (HCTZ; 12.5 mg) and placebo in 194 patients with type 2 diabetes mellitus and hypertension for 4 weeks using ambulatory blood pressure monitoring. Endpoints (change from baseline to week 4) were: 24-h mean systolic blood pressure (SBP; primary); daytime, night-time, seated predose SBP, 24-h, daytime, night-time, seated predose diastolic blood pressure, 24-h urinary glucose excretion and fasting plasma glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 10 publications
1
50
1
Order By: Relevance
“…This effect has been confirmed with all SGLT2 inhibitors [29,40] : canagliflozin [41,42], dapagliflozin [43][44][45], empagliflozin [46], ertugliflozin [47] (Table 1). Generally, the reduction in systolic BP was greater (at least twofold) than the reduction in diastolic BP.…”
Section: ) Blood Pressure Lowering Effects Of Sglt2 Inhibitorsmentioning
confidence: 63%
See 1 more Smart Citation
“…This effect has been confirmed with all SGLT2 inhibitors [29,40] : canagliflozin [41,42], dapagliflozin [43][44][45], empagliflozin [46], ertugliflozin [47] (Table 1). Generally, the reduction in systolic BP was greater (at least twofold) than the reduction in diastolic BP.…”
Section: ) Blood Pressure Lowering Effects Of Sglt2 Inhibitorsmentioning
confidence: 63%
“…Generally, the reduction in systolic BP was greater (at least twofold) than the reduction in diastolic BP. The BP reduction has been demonstrated when BP was controlled in seated position in the investigator office [28,29,45] or during 24h-ambulatory monitoring [44][45][46][47] (Table 2). It has been suggested that circadian BP rhythm may represent a possible key target of SGLT2 inhibitors used for the treatment of Type 2 diabetes [48].…”
Section: ) Blood Pressure Lowering Effects Of Sglt2 Inhibitorsmentioning
confidence: 99%
“…On average, a mild diuretic effect was observed with ertugliflozin 1 mg and 25 mg (24-h urinary volume increase: 126.5 mL and 236.2 mL, respectively), but not with HCTZ (−1.73 mL/day). No significant changes in 24-h mean plasma renin activity or urinary aldosterone were seen with either ertugliflozin or HCTZ [29].…”
Section: Diuretic Effects Of Sglt2 Inhibitorsmentioning
confidence: 83%
“…A 4-week study compared the BP-lowering effects of ertugliflozin (1 mg, 5 mg, 25 mg), HCTZ (12.5 mg) and a placebo in 194 patients with T2D and hypertension [29]. Reductions in SBP were closely similar with ertugliflozin and HCTZ ( Table 2).…”
Section: Diuretic Effects Of Sglt2 Inhibitorsmentioning
confidence: 93%
See 1 more Smart Citation